Port Sustainability as a Service: The Design of Bespoke Service Level Agreements (SLAs) to Improve Operational Efficiency at Harbours by Prioritising Social Satisfaction - Peoples, Cathryn; Moore, Adrian; Georgalas, Nektarios (Frontiers in Sustainability, 2022)
The maritime industry is a complex ecosystem which is important to manage carefully given its handling of global trade. Effective operation at a port is dependent on a timely passage of goods, involving multiple competing objectives, one of which is sustainability. Unsurprisingly, given the extent of a port’s operations, it is a significant contributor of emissions. A port is a physically demanding industry in which to work, and any degradation in workforce productivity can have a detrimental effect on the port’s effective running. Slow operations, combined with dependencies between a port’s stakeholders, can further amplify unsustainability. There are some efforts to explore the digitalization of ports, including the creation of smart ports. However, there is widespread resistance to the introduction of technology in this domain. There are therefore a number of areas in which to make technical contributions to improve the efficiency of port operations. In this paper, we propose using the satisfaction of staff at a port to assess the efficiency of its operations. This will be possible through the roll-out of sensors supporting an Internet of Things (IoT) architecture across the port, with the intention of improving operational efficiencies. With operational latencies as expected, we argue that staff will be satisfied, however, once delays become more unpredictable and unexpected, staff satisfaction will decline. It is therefore through increased IoT use that port sustainability will be supported. To enable this, staff satisfaction can be monitored and managed using Service Level Agreements (SLAs). When staff are satisfied, the port will be operated and sustain low costs. When staff satisfaction begins to decline, however, operation will become more focused on the performance of the port, with a view to improving it through identifying where bottlenecks exist from the perspective of inefficient operations and subsequently, staff output. While simultaneously managing both cost and performance through the satisfaction of staff, the goal is an overall positive contribution to a port’s efficiency and sustainability.